2018
DOI: 10.1136/jramc-2018-001001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of one session of mirror therapy on phantom limb pain and recognition of limb laterality in military traumatic lower limb amputees: a pilot study

Abstract: Up to 70 % of military amputees suffer phantom limb pain (PLP), which is difficult to treat. PLP has been attributed to cortical reorganisation and associated with impaired laterality. Repeated sessions of mirror therapy (MT) can benefit PLP; however, anecdotal evidence suggests one MT session could be effective. In a one-group pretest and post-test design, 16 UK military unilateral lower limb amputees (median age: 31.0, 95% CI 25.0 to 36.8 years) undertook one 10 min MT session. Visual analogue scale (VAS) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 26 publications
(36 reference statements)
0
17
0
1
Order By: Relevance
“…In 84% of works, no information about the race or ethnicity of participants was reported. [28][29][30][31][32][35][36][37][38][39][40][41][42][43][44][45][46][47][48]50,[52][53][54][55][56][57][58][59][60][63][64][65][67][68][69][71][72][73][74][77][78][79][80][81][82][83][84][85][86][87][88] Some works included participants within a narrow age range (e.g. 20-30 years old…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 84% of works, no information about the race or ethnicity of participants was reported. [28][29][30][31][32][35][36][37][38][39][40][41][42][43][44][45][46][47][48]50,[52][53][54][55][56][57][58][59][60][63][64][65][67][68][69][71][72][73][74][77][78][79][80][81][82][83][84][85][86][87][88] Some works included participants within a narrow age range (e.g. 20-30 years old…”
Section: Resultsmentioning
confidence: 99%
“…Fifty-six works (92%) used only one of the phases of graded motor imagery, [28][29][30][31][32][33][34][35][37][38][39][40][41][42][43][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]74,[76][77][78][79][80][82][83][84][85]87,89 and only two works (3%) used all three graded motor imagery phases. 36,86 Figure 5 summarizes the number of works using each phase.…”
Section: Resultsmentioning
confidence: 99%
“…While a number of studies and groups have independently demonstrated a benefit from using mirror therapy in the treatment of phantom limb pain (Ramachandran and Rogers-Ramachandran, 1996; MacLachlan et al, 2004; Chan et al, 2007; Sumitani et al, 2008; Mercier and Sirigu, 2009; Finn et al, 2017; Ol et al, 2018), other groups have not reported similar successes (Brodie et al, 2007; Thieme et al, 2016; Richardson and Kulkarni, 2017; Wareham and Sparkes, 2018). In this study we followed mirror therapy treatment protocols that had previously been shown to be effective compared with limb movements alone (mirror covered) or imagined movement in a randomized, controlled, cross-over design (Chan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…All of these may have influence on the effectiveness of mirror therapy. It is also worth noting that those groups which did not report PLP reduction employed only a single session of mirror therapy (Brodie et al, 2007; Wareham and Sparkes, 2018), whereas the studies demonstrating efficacy of the therapy had sustained treatment sessions of a period of time. Recently, it was reported that amputee with greater severity of PLP require a longer duration of treatment (more sessions) before an effect can be seen, compared to fewer treatment sessions required for pain reduction in amputees with less severe phantom pain (Griffin et al, 2017), and this finding likely affects the negative conclusions drawn from analyses of prior studies (Thieme et al, 2016; Richardson and Kulkarni, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Na correlação feedback e Realidade Virtual/Aumentada, Perry et al (2013) aborda o uso eficaz de um Ambiente de Integração Virtual na analgesia não somente de pacientes que referem a dor no membro fantasma, como também na condição da dor do membro residual, que acomete principalmente militares amputados.Em estudo anterior,Osumi et al (2017) também abordou o uso da Realidade Virtual na analgesia da dor do membro fantasma, mas dessa vez concluiu houve melhoria das representações de movimento deste membro, em uma sessão de curta duração. Em um comparativo de tratamentos,Wareham et al (2020) utilizou a terapia de espelho em militares amputados, também em uma sessão de curta duração, mas não alcançou resultados consideráveis no tratamento da dor do membro fantasma. As diferenças podem-se advir de diferenças nos quadros dos pacientes, como por exemplo, o formato ao qual foi realizada a amputação: cirúrgica ou traumaticamente, dentre outros fatores.…”
unclassified